2014
DOI: 10.1097/mjt.0b013e31824567fe
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim-Sulfamethoxazole Induced Rhabdomyolysis

Abstract: Empiric antibiotic usage is very common in clinical practice and Trimethoprim-Sulfamethoxazole (TMP-SMX) is one such antibiotic used extensively in primary care practice. Some patients experience serious adverse effects to the antibiotics that markedly increase the morbidity and the cost of medical care. We describe one such patient, a previously healthy 40-year-old Hispanic female who developed myositis and rhabdomyolysis secondary to TMP-SMX. To the best of our knowledge, this is the first report of TMP-SMX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Our results demonstrated significant rhabdomyolysis associations (from strongest to weakest) with daptomycin, cefditoren, cefaclor, erythromycin, norfloxacin, clarithromycin, meropenem, azithromycin, cefdinir, piperacillintazobactam, trimethoprim-sulfamethoxazole, linezolid, and ciprofloxacin. Our results confirmed previously known rhabdomyolysis associations with daptomycin, macrolides, trimethoprimsulfamethoxazole, linezolid, fluoroquinolones, and cefdinir [2][3][4][5][6][7][8][9][10][11][12][13][14]. Meropenem, cefditoren, cefaclor, and piperacillin-tazobactam were found to be associated with rhabdomyolysis, which were not reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrated significant rhabdomyolysis associations (from strongest to weakest) with daptomycin, cefditoren, cefaclor, erythromycin, norfloxacin, clarithromycin, meropenem, azithromycin, cefdinir, piperacillintazobactam, trimethoprim-sulfamethoxazole, linezolid, and ciprofloxacin. Our results confirmed previously known rhabdomyolysis associations with daptomycin, macrolides, trimethoprimsulfamethoxazole, linezolid, fluoroquinolones, and cefdinir [2][3][4][5][6][7][8][9][10][11][12][13][14]. Meropenem, cefditoren, cefaclor, and piperacillin-tazobactam were found to be associated with rhabdomyolysis, which were not reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…A review of 53 cases showed rhabdomyolysis associated with concomitant use of statins and azithromycin [7]. Additionally, case reports indicated that trimethoprim-sulfamethoxazole induced rhabdomyolysis occurred in both immunocompetent and immunocompromised patients [8,9]. There have been case reports linking the use of linezolid to serious cases of rhabdomyolysis [10,11].…”
Section: Ivyspringmentioning
confidence: 99%
“…Trimethoprim-sulfamethoxazole: There have been several reports of trimethoprim-sulfamethoxazole-induced rhabdomyolysis in immunocompromised patients [ 36 39 ], but it seems to be very rare in the immunocompetent patients. To our knowledge, only two cases of trimethoprim-sulfamethoxazole-induced rhabdomyolysis have been reported in immunocompetent patients [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first case series (Case 1 in Table 1) that is of an immunocompetent patient with SMX-TMP-induced rhabdomyolysis by Ainapurapu and Kanakadandi was very similar to our patient in that they were both females in their early 40's, being treated empirically with SMX-TMP for a suspected UTI and experiences an onset of bilateral leg pain on day 2 of therapy [14]. However, no confounding [A] : empiric treatment for presumed UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature found most of the reported cases being in immunocompromised patients with HIV infection [10] [11] [12], or allogeneic stem cell transplant recipient [11] [13]. To the best of our knowledge, our patient is the third case of SMX-TMP-induced rhabdomyolysis in an immunocompetent patient, and the second of the immunocompetent patient to have multiple attributing factors [14] [15]. Verbal consent was obtained from the patient to discuss her case.…”
Section: Introductionmentioning
confidence: 99%